Analysis of Temperature, Stress and Displacement Distribution under Freeze-Thaw Considering the Influence of Initial Boundary and Insulation Layers. Issue 1 (February 2021) - Zhang, Xiaomei; Jiang, Mingjun; Wang, Shijun; Zhang, Zhe
Abstract: The freeze-thaw disaster in seasonally frozen soil area are challenging the operation safety of power transmission and transformation projects. The distribution of soil temperature and deformation laying below the foundation is significant to the soil stability in seasonally frozen soil area. The temperature distribution of the foundation is closely related to the external temperature, the thermal field of bottom boundary and the materials of insulation layers. In this paper, the typical tower foundation of 750 kV Gansu Hexi power grid project and the geological conditions of Shulehe area in Gansu Province were selected as the investigation site, and the theoretical analysis and numerical simulation methods are used to analyze the thermal-mechanical coupling considering different boundaries. The deformation, stresses and temperature changes of tower foundation and surrounding soil under different thermal protection structures were discussed. Through comparative analysis, it was found that the optimized structure can effectively improve the soil temperature in extreme environment, avoid frost heave, and meet the design requirements of bearing capacity.